Proton exchange membrane fuel cell (PEMFC) parameters estimation using time-frequency analysis technique - Razali, Muhammad Zuhaili (2017)
Proton Exchange Membrane Fuel cell (PEMFC) is a device that converts chemical energy into electrical energy. The performance characteristics of the PEMFC are affected by many factors either from PEMFC design specification or from the operating conditions. Improper handling the operating condition of the PEMFC will cause failure and damage to the entire system. Thus, the system needs the accurate information about the performance characteristics of PEMFC at various operating conditions with changing load demand to prevent the PEMFC from damage. In this research, periodogram and spectrogram techniques are proposed in order to determine the hydrogen (H2) inlet pressures and stack temperature performance characteristics of PEMFC. Firstly, the signal voltages of various PEMFC operating conditions are captured by using oscilloscope. The raw signals from oscilloscope are then transformed into periodogram and time-frequency distribution (TFD) which is spectrogram. The signal parameter that desired to be extracted from spectrogram are instantaneous voltage of direct current (VDC), voltage of root mean square (VRMS), and voltage of alternating current (VAC) parameters. From the parameter estimation curves and the three-dimensional maps of H2 inlet pressures result, the highest values of instantaneous VRMS and VDC are obtained at a pressure of 0.5 bars, whereby the lowest values are obtained at a pressure of 0.1 bars. These parameters are highest in open voltage conditions but decrease gradually with increasing load demand up to 35 A. The highest values of parameter estimation curves and the three-dimensional maps of stack temperatures are obtained at 40 °C whereas the lowest values are obtained at 20 °C. These parameters are highest at open voltage conditions but decrease gradually with an increase in the load demand up to 18 A. The absolute percentage error (APE) and mean absolute percentage error (MAPE) are used to justify the performance analysis of the spectrogram parameters. The highest APE is attained at a load demand of 15 A, with a value of 0.76% whereas the highest MAPE is obtained for a stack temperature of 25 °C with a value of 0.334%. Based on the results, the estimation of the VDC parameter from TFD technique for both H2 inlet pressure test and stack temperature test are acceptable since the APE and MAPE values are less than 1%. The outcome of this research verifies that the TFD technique clearly gives the information of the performance characteristics of PEMFC at various operating conditions with changing load demand.